Empowering School Students through Developing Critical Thinking Skills - Dogra, Bharti (JOURNAL OF INDIAN EDUCATION, 2020)
Developing critical thinking has always remained one of the primary goals of school education. Critical thinking emphasises on thinking, challenging the validity of prior beliefs and assumptions. A person having critical thinking skills is expected to adopt an objective and questioning perspective. Can critical thinking be developed? Can students acquire critical thinking? What is the role of a teacher in developing critical thinking of the students? How can we as teachers initiate and sustain a classroom environment which is conducive for development of critical thinking of students? This paper tries to answer these questions through analysis of various strategies which can be used by teachers for developing critical thinking amongst students. Critical thinking is a skill and it can be acquired by students.